(untitled) (2013)
In recent years, the software outsourcing (SO) strategy for organizations has become a useful and important alternative, as well as SO projects. SO projects have many complexities due to several factors affecting management. These complexities and importance of SO require that successfull projects meet a parameter set: budget, cost, schedule, among others. This requirement can be met through the implementation of methods and techniques of risk management (RM). RM is a process to prevent problems, establish actions to follow, and monitor the project to ensure success. Likewise, it is considered a key process in making decisions about risks. In this paper, we present a proposal for the risks identification related to software outsourcing process. Risk identification is the basic activity on which rests the success of RM process. Our proposal is a risk taxonomy of SO, consisting in a hierarchical classification structure based on the RM of SO projects. The taxonomy was validated in a study case: Project of pre-developed software acquisition. The results have been useful for the organization and for the refinement of the proposal, thanks to lessons learned.